Artificial Intelligence and Sustainable Energy Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This topic has been successfully completed. A total of 180 scientific articles were sent, of which 66 have been accepted for publication. These 66 articles are published in this reprint.